Agenda Setting During Follow-Up Encounters in a University Primary Care Outpatient Clinic. Issue 6 (3rd June 2017) - Rey-Bellet, Sarah; Dubois, Julie; Vannotti, Marco; Zuercher, Marili; Faouzi, Mohamed; Devaud, Karen; Rodondi, Nicolas; Rodondi, Pierre-Yves
ABSTRACT: At the beginning of the medical encounter, clinicians should elicit patients' agendas several times using open-ended questions. Little is known, however, about how many times physicians really solicit a patient's agenda during follow-up encounters. The objective was to analyze the number of agenda solicitations by physicians, of agendas initiated by physicians, and of patients' spontaneous agendas during the beginning and the entire encounter. We analyzed 68 videotaped follow-up encounters at a university primary care outpatient clinic. The number of different types of agenda setting was searched for and analyzed using negative binomial regression or logistic regression models. Physicians solicited agendas a mean ± SD of 0.8 ± 0.7 times/patient during the first 5 minutes and 1.7 ± 1.2 times/patient during the entire encounter. Physicians in 32.4% of encounters did not solicit the patient agenda, and there were never more than two physician's solicitations during the first 5 minutes. The mean number of physician's solicitations of the patients' agenda was 42% lower among female physicians during the first 5 minutes and 34% lower during the entire encounter. The number of agendas initiated by physicians was 1.2 ± 1.2/patient during the beginning and 3.2 ± 2.3/patient during the entire encounter. In 58.8% of the encounters, patients communicated their agendas spontaneously. There were twice as many patient spontaneous agendas (IRR = 2.12, p = .002) with female physicians than with males. This study showed that agenda solicitation with open-ended questions in follow-up encounters does not occur as often as recommended. There is thus a risk of missing new agendas or agendas that are important to the patient.